2017
DOI: 10.1007/s10646-017-1781-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic and pulse exposure effects of silver nanoparticles on natural lake phytoplankton and zooplankton

Abstract: The increasing use of silver nanoparticles (AgNPs) in consumer products raises concerns regarding the environmental exposure and impact of AgNPs on natural aquatic environments. Here, we investigated the effects of environmentally relevant AgNP concentrations on the natural plankton communities using in situ enclosures. Using twelve lake enclosures, we tested the hypotheses that AgNP concentration, dosing regimen, and capping agent (poly-vinyl pyrrolidone (PVP) vs. citrate) exhibit differential effects on plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 65 publications
3
13
0
2
Order By: Relevance
“…Diversity, total biomass, and total pigments also showed no correlation with total silver concentrations or particulate silver concentrations indicating a higher influence of natural variables. Similar to the results of a several week long, lake mesocosm study with AgNPs, at the longer temporal scale natural variability in our ecosystem outweighs any effects the AgNPs may be causing on algal communities (Vincent et al ). It is also possible that in both of these studies natural variables such as dissolved organic matter (DOM) and dissolved ions are helping to increase AgNP stability, which can decrease toxic effects to organisms such as algae (Sharma et al ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Diversity, total biomass, and total pigments also showed no correlation with total silver concentrations or particulate silver concentrations indicating a higher influence of natural variables. Similar to the results of a several week long, lake mesocosm study with AgNPs, at the longer temporal scale natural variability in our ecosystem outweighs any effects the AgNPs may be causing on algal communities (Vincent et al ). It is also possible that in both of these studies natural variables such as dissolved organic matter (DOM) and dissolved ions are helping to increase AgNP stability, which can decrease toxic effects to organisms such as algae (Sharma et al ).…”
Section: Discussionsupporting
confidence: 85%
“…We also did not account for the effect of AgNPs on other foodweb components, specifically zooplankton grazers which may be more susceptible to AgNPs than phytoplankton (Griffitt et al 2008). However, a lake mesocosm study at the IISD-ELA found that PVP-capped AgNPs only had subtle effects on the zooplankton community and that these effects had no impact the phytoplankton, so we feel this is likely the case for our study as well (Vincent et al 2017). Despite these limitations, we nonetheless provide strong evidence that phytoplankton communities do not respond to environmentally relevant concentrations of AgNPs at seasonal scales across 2 yr and that natural seasonal an climatic drivers exert stronger effects on community dynamics at longer time scales.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Отже, НЧAg спричиняють вищу токсичність у природних екосистемах, ніж у лабораторних. Однак результати досліджень у природних середовищах доводять меншу токсичність НЧAg [26,27], що підкреслює важливість досліджень у природних середовищах.…”
Section: різні розміри і форми частинок нчAg у лабораторних та природних середовищахunclassified
“…<1 week) conducted in microcosms [ 9 , 19 ] and in larger mesocosms [ 20 ]. Over longer time scales ranging up to several weeks, AgNP fate has been studied in a wetland mesocosm [ 8 ], in mesocosms placed in a lake [ 21 24 ] and in an estuary [ 25 ]. In general, these studies in mesocosms and microcosms indicate that the concentrations of Ag + are low in the natural aquatic environment because of rapid binding to organic and inorganic ligands [ 20 , 21 , 25 ].…”
Section: Introductionmentioning
confidence: 99%